A STUDY OF SEASONAL INFLUENZA AND HEALTH GIRLS, AWARENESS ABOUT ITS VACCINE IN AL-RIFAI DISTRICT - Gouda, Sarah Aziz Askar; Majeed, Zahraa Jasim Hammoodi; Abbas, Marwa Shaalan Ghali; Malhak, Qayed Darwish ḵhasara; Ali, Zahraa Ahmed Mohsen Muhammad (Journal of Medical Genetics and Clinical Biology, 2024)
The influenza virus (IV) is still of great importance as it poses an imminent threat to humans and animals. Among the three IV-types (A, B, and C) influenza A viruses are clinically the most important being responsible for severe epidemics in humans and domestic animals. Aerosol droplets transmit the virus that causes a respiratory disease in humans that can lead to severe pneumonia and ultimately death. The high mutation rate combined with the high replication rate allows the virus to rapidly adapt to changes in the environment. Thereby, IV escape the existing immunity and become resistant to drugs targeting the virus. This causes annual epidemics and demands for new compositions of the yearly vaccines. Furthermore, due to the nature of their segmented genome, IV can recombine segments. This can eventually lead to the generation of a virus with the ability to replicate in humans and with novel antigenic properties that can be the cause of a pandemic outbreak. For its propagation the virus binds to the target cells and enters the cell to replicate its genome. Newly produced viral proteins and genomes are packaged at the cell membrane where progeny virions are released. As all viruses IV depends on cellular functions and factors for their own propagation, and therefore intensively interact with the cells. This dependency opens new possibilities for anti-viral strategies